Reframing Qur’anic Ethical Education for the Contemporary World: Toward Social Harmony and Religious Tolerance - Supandi; Subhan, Moh; Hobir, Abdul; Aini, Kurratul; Mawardi Syufyan, Farid (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This study examines how Qur’anic ethical education can be reconstructed as a pedagogical framework for promoting social harmony and religious tolerance in contemporary plural societies. The article departs from the widespread perception that the Qur’an is incompatible with tolerance because it is often interpreted literally and selectively, especially in relation to verses on war and unbelief. In contrast, this study argues that the dominant ethical orientation of the Qur’an is justice, compassion, recognition of diversity, dialogue, and peace. Using qualitative library research with a descriptive-interpretive design, the study employs thematic (maudhu‘i) and maqāṣidī approaches to analyze eighteen Qur’anic verses concerning freedom of religion, diversity, relations with non-Muslims, and reconciliation. The analysis is supported by classical and contemporary tafsir, particularly Tafsīr al-Ṭabarī, Ibn Kathīr, Tafsīr al-Manār, and Tafsir al-Mishbah. The findings reveal five central Qur’anic ethical values; ‘adl, raḥmah, ta‘āruf, shūrā, and ṣulḥ/salām; which together form the basis of a reconstructed model of Qur’anic ethical education. These values are operationalized through five educational dimensions: educational goals, curriculum, pedagogy, institutional culture, and assessment. The study concludes that Qur’anic ethical education should move beyond doctrinal transmission and ritual piety toward the cultivation of empathy, intercultural competence, dialogue, and peaceful conflict resolution. Contribution: The study contributes by reframing Qur’anic ethics as a transformative and measurable pedagogical model that integrates justice, compassion, dialogue, and recognition of diversity into Islamic education in order to strengthen social harmony and religious tolerance in plural societies.